Impact of Irrigation and Levels of Fertilizers Application on Zero Tilled Cowpea (Vigna unguiculata L.) Cultivation - GAME, V. N.; MAHADKAR, U. V.; KHETRE, O. S.; SUTAR, V. K. (Journal of the Indian Society of Coastal Agricultural Research, 2023)
An experiment was conducted at Agronomy farm of Dr. B. S. Konkan Krishi Vidyapeeth, Dapoli during Rabi season of 2011-2012 to study the effect of irrigation and levels of fertilizer application on yield, quality and nutrient uptake of zero tilled cowpea. The experiment was laid out in split plot design with three replications. The main plot treatments were three irrigation levels viz., no irrigation, one irrigation at branching and two irrigations at branching and pod filling stage. The sub plot treatments comprised six fertilizer levels viz., no fertilizer, 25% RDF below seed placement, 50% RDF below seed placement, 75% RDF below seed placement, 100% RDF below seed placement and 100% RDF through line application. Results revealed that application of two irrigations (at branching and pod filling) recorded significantly higher grain yield, stover yield, protein content as well as N, P2O5 and K2O content and their uptake followed by treatments in which one irrigation (at branching) and zero irrigation (control). Application of 100% RDF below seed placement recorded significantly higher grain yield, stover yield, protein content as well as N, P2O5 and K2O content and their uptake followed by 100% RDF through line application, 75, 50, 25% RDF below seed placement and control.